2003
DOI: 10.1161/01.cir.0000068376.88600.41
|View full text |Cite
|
Sign up to set email alerts
|

Role of L-Type Calcium Channels in Pacing-Induced Short-Term and Long-Term Cardiac Memory in Canine Heart

Abstract: Background-We tested the hypothesis that I Ca,L is important to the development of cardiac memory. Methods and Results-The effects of L-type Ca 2ϩ channel blockade and ␤-blockade were tested on acutely anesthetized and on chronically instrumented, conscious dogs. Short-term memory (STM) was induced by 2 hours of ventricular pacing and long-term memory (LTM) by ventricular pacing for 21 days. STM dogs received placebo, nifedipine, or propranolol, and LTM dogs received placebo, atenolol, or amlodipine. AT 1 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 24 publications
(26 reference statements)
6
82
0
Order By: Relevance
“…12 Changing the I to and I Ca,L current size is realized by changing g to and g Ca,L , respectively. Plotnikov et al 49 observed a more positive activation and slower inactivation of I Ca,L in patch-clamp experiments. To account for the shift in I Ca,L activation, I Ca,L kinetics are changed by adaption of the dynamics of activation gating variable d. In the Courtemanche-Ramirez-Nattel model, the dynamics of d are defined by…”
Section: Cardiac Cycle Simulationmentioning
confidence: 96%
See 4 more Smart Citations
“…12 Changing the I to and I Ca,L current size is realized by changing g to and g Ca,L , respectively. Plotnikov et al 49 observed a more positive activation and slower inactivation of I Ca,L in patch-clamp experiments. To account for the shift in I Ca,L activation, I Ca,L kinetics are changed by adaption of the dynamics of activation gating variable d. In the Courtemanche-Ramirez-Nattel model, the dynamics of d are defined by…”
Section: Cardiac Cycle Simulationmentioning
confidence: 96%
“…Furthermore, we model the changes in I Ca,L kinetics as observed by Plotnikov et al 49 after ventricular pacing.…”
Section: Cardiac Cycle Simulationmentioning
confidence: 99%
See 3 more Smart Citations